2014
DOI: 10.1088/0004-637x/787/2/166
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATING THE TeV MORPHOLOGY OF MGRO J1908+06 WITH VERITAS

Abstract: We report on deep observations of the extended TeV gamma-ray source MGRO J1908+06 made with the VERITAS very high energy gamma-ray observatory. Previously, the TeV emission has been attributed to the pulsar wind nebula (PWN) of the Fermi-LAT pulsar PSR J1907+0602. We detect MGRO J1908+06 at a significance level of 14 standard deviations (14σ ) and measure a photon index of 2.20 ± 0.10 stat ± 0.20 sys . The TeV emission is extended, covering the region near PSR J1907+0602 and also extending toward SNR G40.5-0.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 32 publications
6
64
0
Order By: Relevance
“…Over 15 sources within this region were discovered by H.E.S.S. Similar surveys within this region have been performed by Milagro (Abdo et al 2007) and ARGO (Bartoli et al 2013b), along with targeted observations by the IACTs VERITAS and MAGIC (for example, Albert et al 2006;Acciari et al 2009;Aleksić et al 2012Aleksić et al , 2014Aliu et al 2014a). At lower energies, the Fermi Large Area Telescope (Fermi-LAT) has published its third source catalog in the 100 MeV-300 GeV energy range (3FGL), based on the first four years of science operation (Acero et al 2015).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Over 15 sources within this region were discovered by H.E.S.S. Similar surveys within this region have been performed by Milagro (Abdo et al 2007) and ARGO (Bartoli et al 2013b), along with targeted observations by the IACTs VERITAS and MAGIC (for example, Albert et al 2006;Acciari et al 2009;Aleksić et al 2012Aleksić et al , 2014Aliu et al 2014a). At lower energies, the Fermi Large Area Telescope (Fermi-LAT) has published its third source catalog in the 100 MeV-300 GeV energy range (3FGL), based on the first four years of science operation (Acero et al 2015).…”
Section: Introductionmentioning
confidence: 60%
“…and VERITAS and in agreement with Milagro given the statistical uncertainties of both instruments. Aliu et al (2014a) reported strong excess near the pulsar PSR J1907+0602 but also extends toward SNR G 40.5-0.5. The Pass 1 data set is not able to resolve the spatial morphology of this source.…”
Section: Source Detectionsmentioning
confidence: 92%
See 1 more Smart Citation
“…There has been recent discussion about the possibility that the nearby gamma-ray pulsar J1907+0602 (Abdo et al 2009) might be associated with G40.5-0.5 because of its association with the nearby TeV source MGRO J1908+06 (Abdo et al 2007) which extends to include the lower limb of the remnant closest to PSR J1907+0602 (see Figure 1 of Aliu et al (2014)). Abdo et al (2010) found that this pulsar (yellow cross in Figure 6) lies in the extended emission seen also with the High Energy Stereoscopic System (HESS; Aharonian et al 2009) and the Very Energetic Radiation Imaging Telescope Array System (VERITAS; Ward 2008).…”
Section: Psr J1907+0631mentioning
confidence: 99%
“…Tests on these datasets will provide a check of the extended source fitting using a source with a known spectrum. Finally, the technique will be applied to known extended sources such as supernova remnant G106.3+2.7 [10] and MGRO J1908+06 [11]. Each check is designed to ensure all components of the MLM are understood and behave as expected as well as to identify regions where the technique struggles.…”
Section: Pos(icrc2015)1031mentioning
confidence: 99%